Innovation, development and digital transformation of foreign trade, an analysis of the latest research in Asia Pacific - Carbajal Ruiz, Mauro; Gonzales Roldan, Valeria Ivonne; Parodi Rojas, Luciana; Reusche Marchena, Milagros De Fatima; Romero Zuppiani, Cristobal Andres; Azabache Moran, Carlos Alberto; Moscoso Cuaresma, Julio Ricardo (LACCEI, 2023)
Over the last few years, a marked increase in innovation and digital transformation processes in the field of foreign trade has been evident. While it is true that this drive towards transformation and innovation experienced a notable acceleration because of the outbreak of the COVID-19 pandemic in 2020, it is undeniable that both transformation and continuous development continue to be the fundamental pillars that allow companies transcend and expand over time. In this context, the academic sphere has devoted increasing attention to entrepreneurial exploration. In line with this line of research, the central purpose of this article lies in the identification of emerging trends in innovation, development, and digital transformation in the field of foreign trade, as emerged from the most recent investigations carried out in the region of Asia Pacific during the years 2012 and 2022. The methodology used the systematic review under a qualitative approach and bibliographic nature. This approach implies a thorough analysis of various academic sources, among which renowned repositories such as Scopus, Science Direct and Web of Science stand out. The emanated results are based on a bibliographic corpus made up of a total of 47 research articles. As conclusions drawn from this research, the presence of unequivocal trends in relation to digital innovation, development, and digital transformation in the field of foreign trade in the Asia Pacific region stands out. These trends, shaped by economic, technological, and social conditions, present a set of essential perspectives for the evolving future of business practices in the region.